Information architecture for serial and scientific publications. The case of the Cuban Journal of Audiovisual Research - Paz Enrique, Luis Ernesto; Artigas Morales, Wileidys; Hernández Alfonso, Eduardo Alejandro (Cuadernos de Documentación Multimedia, 2019)
Serials and scientific publications have the mission to disseminate scientific knowledge. The use of automated systems for managing online journal favors that publication are indexed easily. There are no scientific documents reflect the information architecture of Open Journal Systems. There are also a small serials and scientific publications that approach the topic of research in audiovisual media. It is proposed as objective of the study: to design a serial and scientific publication specializing in disseminating articles on the subject of audiovisual research, from the use of Open Journal Systems and describe the information architecture of the tool mentioned. For collect the information are use methods and techniques in the theoretical and empirical levels, plus a methodology for designing information architecture. Is designed a scientific publication based on the user experience for the socialization of research in the audiovisual topic. Information architecture guidelines are established that should be followed by publications that use the Open Journal Systems as an automated system in editorial management.
Keywords: Online serial publication; Open Journal Systems; audiovisual media; users; information architecture